2002
DOI: 10.1590/s1516-31802002000400001
|View full text |Cite
|
Sign up to set email alerts
|

Should we spend less or control a greater percentage of hypertensive patients?

Abstract: Adherence to hypertension treatment forms a major challenge because, despite the relatively simple and cheap diagnosis combined with efficacious treatments, the majority of patients do not adhere to the treatment and do not present controlled arterial pressure. A large number of factors have been related to low adherence rates. 1When we asked patients in our service (n = 353) regarding the causes of low adherence, we obtained the following results: a) medicines -high cost (89%), taking them several times per d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Nevertheless, Brazilian pharmacoeconomic studies related to hypertension have been rare (5). The few studies that have examined antihypertensive treatment costs in Brazil concluded that diuretics and beta-blockers are more cost-effective than other classes of antihypertensive drugs (6).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Brazilian pharmacoeconomic studies related to hypertension have been rare (5). The few studies that have examined antihypertensive treatment costs in Brazil concluded that diuretics and beta-blockers are more cost-effective than other classes of antihypertensive drugs (6).…”
Section: Introductionmentioning
confidence: 99%